Tracking a Fast-Moving Disease: Longitudinal Markers, Monitoring, and Clinical Trial Endpoints in ALS - Chipika, Rangariroyashe Hannah; Finegan, Eoin; Li Hi Shing, Stacey; Hardiman, Orla; Bede, Peter (Frontiers in Neurology, 2019)
Amyotrophic lateral sclerosis encompasses a heterogeneous group of phenotypes with different progression rates, varying degree of extra-motor involvement and divergent progression patterns. The natural history of ALS is increasingly evaluated by large, multi-time point longitudinal studies, many of which now incorporate presymptomatic and post mortem assessments. These studies not only have the potential to characterise patterns of anatomical propagation, molecular mechanisms of disease spread, but also to identify pragmatic monitoring markers. Sensitive markers of progressive neurodegenerative change are indispensable for clinical trials and individualised patient care. Biofluid markers, neuroimaging indices, electrophysiological markers, rating scales, questionnaires and other disease-specific instruments have divergent sensitivity profiles. The discussion of candidate monitoring markers in ALS has a dual academic and clinical relevance, and is particularly timely given the increasing number of pharmacological trials. The objective of this paper is to provide a comprehensive and critical review of longitudinal studies in ALS, focussing on the sensitivity profile of established and emerging monitoring markers.